The Dynamics of Social Network Structures and Contestation in the Collaborative Management of Lake Tempe in South Sulawesi - Muhammad Said; Bevaola Kusumasari; M. Baiquni; Subando Agus Margono (Policy & Governance Review, 2018)
In managing common pool resources; ideally, it was carried out using a co-management approach that facilitated the cooperation, sharing of power, and responsibility among actors. However, this is quite difficult to achieve since each actor competes against each other’s interests. Such cooperation and competition between actors will form a structure of social networks. This study aims to explain the dynamics of the formation of social network structures based on the cooperation and competition among actors in the management of Lake Tempe, a common pool resource crossing Wajo, Soppeng and Sidenreng Rappang Regencies in South Sulawesi Province. This is a qualitative study with explanatory case study approach, using two data collection techniques: participatory observation and in-depth interview with the government, fishermen, businessmen, and NGOs. This study found that the formation process of the social network structure in the management of Lake Tempe is a dynamic interaction among actors, i.e., cooperation in one side and competition on the other side, forming a social networking structure in two types: centrality and heterogeneity network. Network centrality occurs at the level of decision-making, the rules of play, and the allocation of resources, which is dominated by government actors, while heterogeneity network is dominated by communities that are still maintaining social capital such as kinship as well as knowledge and resources sharing. Brokerages, those who link the advantaged groups (local government and big-scale-fisherman/Pallawang) with the disadvantaged (small-scale-fisherman/ Pakkajalalla) do not exist in the management. Although the existence of brokerages is potential, they may also have a conflict of interest, since authorities and economic factors will be their target.